MOTIVATIONAL FACTORS AFFECTING ENGLISH SPEAKING PERFORMANCE AMONG UZBEK LEARNERS - Menglibekov Reypnazar Muxammetkarim-uli (Modern American Journals, 2025)
The ability to speak English fluently has become a crucial skill for students in Uzbekistan, where education reforms have placed a growing emphasis on communicative competence. Despite years of classroom instruction, many Uzbek learners still struggle with spoken English, often due to low confidence, lack of practice, or limited exposure to real communication. One of the most influential elements shaping speaking performance is motivation—the internal drive that compels learners to engage, persevere, and succeed in language learning.Motivation influences how often learners practice speaking, how willing they are to take risks in communication, and how they respond to challenges. Understanding the motivational factors behind speaking performance—whether they stem from personal goals, cultural values, educational settings, or external rewards—is essential for improving English language teaching in Uzbekistan.This article examines key motivational influences on Uzbek learners, explores their effects on speaking performance, and offers practical insights for language educators to create more engaging and effective learning environments.
Keywords: Motivation, English speaking skills, Uzbek learners, language learning, speaking performance.